Core competencies for diabetes educators: A scoping review. Issue 4 (July 2019) - Alharbi, Talal; Thomacos, Nikos; McLelland, Gayle
Abstract: Aims: Diabetes educators (DEs) play a major role in diabetes education and management. The aims of this scoping review were to compile the currently identified core competencies for DEs and, to review the currently used criteria to assess DEs' core competencies. Methods: A scoping review was conducted using the methodology of the Joanna Briggs Institute. Five databases (Ovid, CINAHL, Scopus, Web of Science and PubMed) were searched. Keywords as well as inclusion and exclusion criteria were identified as search strategies and study selection for this review. Results: A total of (n = 22) publications comprising sixteen peer-reviewed studies and six professional-organisations (grey literature) were selected for review, as they listed the core competencies of DEs. The most common core competencies were related to knowledge and skills in diabetes self-management education, knowledge of pathophysiology and epidemiology, teaching skills, clinical skills and cultural competency. Evidently, an appropriate tool for assessing DEs' competencies is currently unavailable. Conclusions: Given the importance of diabetes education in the care of people living with diabetes, it is imperative that DEs possess competencies in diabetes education and management. The review also identified the need to develop a globally applicable core competency assessment tool for DEs.